Hydrophobic perfluorinated nanofiber membrane capable of catalytically degrading oily dye and preparation method of hydrophobic perfluorinated nanofiber membrane

By combining modified carbon nanoparticles with perfluoropolymers, a hydrophobic perfluoronan fiber membrane with catalytic degradation function was prepared, which solved the problem of single function of perfluoro fiber membrane in the prior art, and achieved oil-based dyes and oils efficient catalytic degradation and flux enhancement of products.

CN119139932APending Publication Date: 2024-12-17JIANGSU JINYOU NEW MATERIALS CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411269671.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Although the existing perfluoropolymer fiber membranes improve oil permeability when treating oil-containing wastewater, they cannot effectively catalyze and degrade oil-based dyes, and have a single function, and cannot effectively recover and purify oil products.

Method used

Modified carbon nanoparticles combined with perfluoropolymers are used to prepare hydrophobic perfluoro nanofiber membranes through electrospinning technology. The modified carbon nanoparticles are etched by reaction of cobalt nitrate hexahydrate and 2-methylimidazole, and copper nitrate/ Doping silver nitrate improves catalytic activity and enables the fiber membrane to have the function of catalytic degradation of oily dyes.

Benefits of technology

The catalytic degradation efficiency of fiber membranes to oily dyes has been significantly improved to 99.7%, and the flux to kerosene has been increased from below 200L/m2·h·bar to 1433L/m2·h·bar, achieving oil-based products efficient flux and catalytic degradation effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005038328790000081
    Figure BDA0005038328790000081
  • Figure BDA0005038328790000082
    Figure BDA0005038328790000082
  • Figure BDA0005038328790000083
    Figure BDA0005038328790000083
Patent Text Reader

Abstract

The invention relates to the field of nano materials and oil-water separation, and particularly discloses a hydrophobic perfluorinated nanofiber membrane capable of catalytically degrading oily dye and a preparation method of the hydrophobic perfluorinated nanofiber membrane. The invention discloses a hydrophobic perfluorinated nanofiber membrane capable of catalytically degrading oily dye. The hydrophobic perfluorinated nanofiber membrane is obtained by electrostatic spinning of a spinning solution, the spinning solution is prepared from the following components in percentage by weight: 9 to 15 percent of polyvinyl alcohol; 1 to 2 wt% of modified carbon nanoparticles; 0.5-1 wt% of boric acid; the balance of perfluoropolymer dispersion liquid; the modified carbon nanoparticles are prepared from the following raw materials: carbon nanoparticles, cobalt nitrate hexahydrate, 2-methylimidazole, copper nitrate / silver nitrate and a solvent. The hydrophobic perfluorinated nanofiber membrane capable of catalytically degrading the oily dye can be used in a membrane treatment process for oil-water separation, and has the advantages that the oil flux is high, and the catalytic degradation efficiency on the oily dye can reach 99.7%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of nanomaterials and oil-water separation, and more specifically, to a hydrophobic perfluoro nanofiber membrane capable of catalytically degrading oily dyes and a preparation method thereof. Background Art

[0002] The discharge of oily wastewater not only causes serious harm to the aquatic ecosystem, but also results in serious waste of resources. How to quickly and efficiently treat oily wastewater to achieve oil purification and waste oil recovery has become a global research and development topic.

[0003] Membrane separation technology is an efficient oily wastewater treatment technology that uses membrane materials to separate oil from water. Among them, perfluoropolymers are widely used in the preparation of membrane materials due to their excellent heat resistance, chemical resistance, non-stickiness, hydrophobicity, wear resistance, electrical insulation and good thermoplastic processing properties.

[0004] At present, some manufacturers have prepared a lipophilic modified perfluoropolymer membrane in order to improve the permeability of perfluoropolymer fiber membrane to oily liquids, which improves the oil flux. However, the function of this membrane is relatively single and cannot achieve the catalytic degradation of oily dyes well. Summary of the invention

[0005] In order to improve the permeability to oily liquids while giving the fiber membrane a catalytic degradation function for oleophilic fuels, the present application provides a hydrophobic perfluoro nanofiber membrane capable of catalytically degrading oily dyes and a preparation method thereof.

[0006] In a first aspect, the present application provides a hydrophobic perfluoro nanofiber membrane capable of catalytically degrading oily dyes, using the following technical solution: A hydrophobic perfluoro nanofiber membrane capable of catalytically degrading oily dyes, obtained by electrostatic spinning from a spinning solution; The spinning solution is composed of the following components in weight percentage: Polyvinyl alcohol 9-15wt%; Modified carbon nanoparticles 1-2wt%; Boric acid 0.5-1wt%; Perfluoropolymer dispersion balance; The raw materials for preparing the modified carbon nanoparticles include carbon nanoparticles, cobalt nitrate hexahydrate, 2-methylimidazole, copper nitrate / silver nitrate and a solvent.

[0007] By adopting the above technical solution: cobalt nitrate hexahydrate and 2-methylimidazole react to etch carbon nanoparticles, and at the same time introduce copper nitrate / silver nitrate into the lattice to improve the catalytic activity, a modified carbon nanoparticle with adsorption and catalytic degradation effect is obtained. The above modified particles are introduced into the spinning solution and electrospun so that the prepared fiber membrane has the above properties, and the catalytic degradation efficiency of oil dyes (Sudan III) is increased from 0% to 99.7%, and the lipophilicity of the fiber membrane can be effectively improved, and the flux of kerosene is increased from less than 200L / m 2 h·bar significantly increased to 1433L / m 2 ·h·bar.

[0008] Optionally, the preparation method of the modified carbon nanoparticles is: Cobalt nitrate hexahydrate and copper nitrate / silver nitrate are dispersed in a solvent to obtain a mixed solution A; carbon nanoparticles and 2-methylimidazole are dispersed in a solvent to obtain a mixed solution B; the mixed solution A and the mixed solution B are blended, reacted, centrifuged to remove the supernatant, washed, and dried to obtain the product.

[0009] By adopting the above technical scheme: firstly, cobalt nitrate hexahydrate and copper nitrate / silver nitrate, carbon nanoparticles and 2-methylimidazole are prepared into dispersions respectively, so that each component is fully dispersed, and then the mixed liquids A and B are blended and reacted to make the reaction sufficient and improve the modification effect.

[0010] Optionally, in the mixed solution A, the concentration of cobalt nitrate hexahydrate is 8-20 mg / mL, and the concentration of copper nitrate / silver nitrate is 5-15 mg / mL.

[0011] Optionally, in the mixed solution B, the concentration of carbon nanoparticles is 100-800 mg / mL, and the concentration of 2-methylimidazole is 50-70 mg / mL.

[0012] By adopting the above technical solution: when the concentrations of cobalt nitrate hexahydrate, copper nitrate / silver nitrate, carbon nanoparticles, and 2-methylimidazole are within the above ranges, the prepared modified carbon nanoparticles have a stronger effect on improving the flux and catalytic degradation effect of the fiber membrane.

[0013] Optionally, the carbon nanoparticles are one of nanographite powder, graphene, carbon nanotubes, and fullerene.

[0014] Optionally, the solvent consists of anhydrous methanol and anhydrous ethanol in a volume ratio of 7:3.

[0015] Optionally, the perfluoropolymer dispersion is one of a polytetrafluoroethylene dispersion and a tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer dispersion.

[0016] Optionally, the solid content of the perfluoropolymer dispersion is 40%-60%.

[0017] In a second aspect, the present application provides a method for preparing a hydrophobic perfluoro nanofiber membrane capable of catalytically degrading oily dyes, using the following technical solution: A method for preparing a hydrophobic perfluoro nanofiber membrane capable of catalytically degrading oily dyes comprises the following steps: S1, blending polyvinyl alcohol, modified carbon nanoparticles, boric acid and perfluoropolymer dispersion, and defoaming to obtain a spinning solution; S2, electrospinning the spinning solution, and calcining at 350-380° C. for 3-5 hours to obtain.

[0018] By adopting the above technical solution: the process steps are fewer, simple and efficient, which is conducive to the industrial scale-up of the preparation of perfluoro fiber membranes, and the prepared fiber membranes have a large flux and have a good catalytic degradation effect on oily dyes.

[0019] Optionally, the specific parameters of the electrospinning are: voltage 12-18 kV, syringe flow rate 0.6-1.0 mL / min, temperature 35-40° C., and humidity 65-70%.

[0020] In summary, this application has the following beneficial effects: 1. The modified carbon nanoparticles introduced in this application significantly improve the lipophilicity of the prepared perfluoropolymer nanofiber membrane, and at the same time make the nanofiber membrane have the function of catalytic degradation of oily dyes, and the flux of kerosene is increased from less than 200L / m 2 h·bar increased to 1433L / m 2 ·h·bar, increased by an order of magnitude; at the same time, the catalytic efficiency of oil dyes (Sudan III) increased from 0% to 99.7%; 2. In the preparation process of the modified carbon nanoparticles of the present application, copper nitrate or silver nitrate is introduced to improve the catalytic degradation activity. The catalytic efficiency of the fiber membrane for oily dyes (Sudan III) is 99.7%, which is significantly higher than the catalytic efficiency of the fiber membrane without copper nitrate / silver nitrate or the introduction of other nitrates, which is 20.1-32.2%; 3. The method of the present application breaks the singleness of traditional polymer fiber membrane preparation methods (such as NIPS, TIPS method, etc.). The prepared fiber membrane has the basic hydrophobicity and lipophilicity of perfluoropolymer. The introduction of modified carbon nanocarbon particles further enhances the lipophilicity, which significantly improves the oil flux of the membrane. At the same time, the fiber membrane is endowed with the function of catalyzing the degradation of oil dyes (Sudan III). DETAILED DESCRIPTION

[0021] The present application is further described in detail below in conjunction with the examples. The sources of the components are as follows, and the raw materials other than those described below are commercially available: Graphene, the manufacturer is Xiamen Kaina Graphene Technology Co., Ltd.; Carbon nanotubes, manufactured by Shanghai Gaibang Industrial Co., Ltd., model 30#; Nano graphite powder, the manufacturer is Dongguan Tangxia Xiangyang Graphite Products Processing Factory, model number is ST-15000; Fullerene, the manufacturer is Hubei Darli Chemical Co., Ltd., model number is Darl-1; Polyvinyl alcohol, manufacturer is Henan Huide Chemical Products Co., Ltd., model number is 1788; Boric acid, 99% concentration; Polytetrafluoroethylene dispersion, manufacturer is Solvay China, model number is D2711F; Tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer dispersion, manufacturer is Shanghai Fangang Plastic Raw Materials Co., Ltd., model number is D335D.

[0022] Preparation Example 1 A modified carbon nanoparticle is prepared by the following steps: 15 g of cobalt nitrate hexahydrate and 8 g of copper nitrate were added to 1 L of solvent (mixed solution of anhydrous methanol and anhydrous ethanol in a volume ratio of 7:3), and the mixture was stirred at 1000 rpm for 10 min to obtain a mixed solution A; 100 g of carbon nanoparticles (graphene, particle size 100 nm) and 60 g of 2-methylimidazole were added to 1 L of solvent (mixed solution of anhydrous methanol and anhydrous ethanol in a volume ratio of 7:3), and ultrasonicated for 5 min to obtain mixed solution B; Mixed solution A was added to mixed solution B, stirred at 500 rpm for 2 h, allowed to stand for 12 h, and then centrifuged to remove the supernatant. Water twice the volume of the precipitate was added to the obtained precipitate for washing, and dried at 60°C for 12 h.

[0023] Preparation Example 2 A modified carbon nanoparticle is prepared by the following steps: To 1 L of solvent (mixed solution of anhydrous methanol and anhydrous ethanol in a volume ratio of 7:3), 10 g of cobalt nitrate hexahydrate and 8 g of silver nitrate were added, and the mixture was stirred at 1000 rpm for 10 min to obtain a mixed solution A; 600 g of carbon nanoparticles (nanographite powder, particle size 500 nm) and 70 g of 2-methylimidazole were added to 1 L of solvent (mixed solution of anhydrous methanol and anhydrous ethanol in a volume ratio of 7:3), and ultrasonicated for 5 min to obtain mixed solution B; Mixed solution A was added to mixed solution B, stirred at 500 rpm for 2 h, allowed to stand for 16 h, and then centrifuged to remove the supernatant. Water twice the volume of the precipitate was added to the obtained precipitate for washing, and dried at 60°C for 12 h.

[0024] Preparation Example 3 A modified carbon nanoparticle is prepared by the following steps: To 1 L of solvent (mixed solution of anhydrous methanol and anhydrous ethanol in a volume ratio of 7:3), 10 g of cobalt nitrate hexahydrate and 5 g of silver nitrate were added, and the mixture was stirred at 1000 rpm for 10 min to obtain a mixed solution A; 500 g of carbon nanoparticles (carbon nanotubes, particle size 800 nm) and 50 g of 2-methylimidazole were added to 1 L of solvent (mixture of anhydrous methanol and anhydrous ethanol in a volume ratio of 7:3), and ultrasonicated for 5 min to obtain a mixed solution B; Mixed solution A was added to mixed solution B, stirred at 500 rpm for 2 h, allowed to stand for 12 h, and then centrifuged to remove the supernatant. The resulting precipitate was washed with water twice the volume of the precipitate and dried at 60°C for 12 h.

[0025] Preparation Example 4 A modified carbon nanoparticle is prepared by the following steps: 20 g of cobalt nitrate hexahydrate and 15 g of silver nitrate were added to 1 L of solvent (mixed solution of anhydrous methanol and anhydrous ethanol in a volume ratio of 7:3), and the mixture was stirred at 1000 rpm for 10 min to obtain a mixed solution A; 800 g of carbon nanoparticles (fullerene, particle size 600 nm) and 70 g of 2-methylimidazole were added to 1 L of solvent (mixture of anhydrous methanol and anhydrous ethanol in a volume ratio of 7:3), and ultrasonicated for 5 min to obtain a mixed solution B; Mixed solution A was added to mixed solution B, stirred at 500 rpm for 2 h, allowed to stand for 16 h, and then centrifuged to remove the supernatant. The resulting precipitate was washed with water twice the volume of the precipitate and dried at 60°C for 12 h.

[0026] Preparation Example 5 A modified carbon nanoparticle is prepared by the following steps: 8 g of cobalt nitrate hexahydrate and 6 g of silver nitrate were added to 1 L of solvent (mixed solution of anhydrous methanol and anhydrous ethanol in a volume ratio of 7:3), and the mixture was stirred at 1000 rpm for 10 min to obtain a mixed solution A; 500 g of carbon nanoparticles (graphene, particle size 900 nm) and 50 g of 2-methylimidazole were added to 1 L of solvent (mixed solution of anhydrous methanol and anhydrous ethanol in a volume ratio of 7:3), and ultrasonicated for 5 min to obtain mixed solution B; Mixed solution A was added to mixed solution B, stirred at 500 rpm for 2 h, allowed to stand for 20 h, and then centrifuged to remove the supernatant. The resulting precipitate was washed with water twice the volume of the precipitate and dried at 60°C for 12 h.

[0027] Preparation Example 6 A modified carbon nanoparticle is prepared by the following steps: 8 g of cobalt nitrate hexahydrate and 6 g of silver nitrate were added to 1 L of solvent (mixed solution of anhydrous methanol and anhydrous ethanol in a volume ratio of 7:3), and the mixture was stirred at 1000 rpm for 10 min to obtain a mixed solution A; 500 g of carbon nanoparticles (carbon nanotubes, particle size 400 nm) and 70 g of 2-methylimidazole were added to 1 L of solvent (mixture of anhydrous methanol and anhydrous ethanol in a volume ratio of 7:3), and ultrasonicated for 5 min to obtain a mixed solution B; Mixed solution A was added to mixed solution B, stirred at 500 rpm for 2 h, allowed to stand for 24 h, and then centrifuged to remove the supernatant. The resulting precipitate was washed with water twice the volume of the precipitate and dried at 60°C for 12 h.

[0028] Comparative Preparation Example 1 A modified carbon nanoparticle, which is different from Preparation Example 2 in that copper nitrate is not added.

[0029] Comparative Preparation Example 2 A modified carbon nanoparticle, which is different from Preparation Example 2 in that an equal amount of potassium nitrate is used instead of copper nitrate.

[0030] Example 1 A hydrophobic perfluoro nanofiber membrane capable of catalytically degrading oily dyes is prepared by the following steps: S1, 10 kg of polyvinyl alcohol, 1 kg of modified carbon nanoparticles (prepared in Preparation Example 1), 0.5 kg of boric acid and 88.5 kg of perfluoropolymer dispersion (polytetrafluoroethylene dispersion, solid content 40%), stirred at 75 ° C for 2 h, defoamed in a vacuum oven, and obtained a spinning solution; S2, electrospinning the spinning solution (voltage 15 kV, syringe flow rate 0.6 mL / min, temperature 35° C., humidity 65%), taking it out after receiving it for 2 hours, and calcining it at 350° C. for 3 hours to obtain; The test showed that the porosity of the nanofiber membrane was 80% and the average fiber diameter was 220 nm.

[0031] Example 2 A hydrophobic perfluoro nanofiber membrane capable of catalytically degrading oily dyes is prepared by the following steps: S1, 12kg of polyvinyl alcohol, 1.5kg of modified carbon nanoparticles (prepared in Preparation Example 1), 0.6kg of boric acid and 85.9kg of perfluoropolymer dispersion (polytetrafluoroethylene dispersion, solid content 60%), stirred at 80°C for 2h, defoamed in a vacuum oven, and obtained a spinning solution; S2, electrospinning the spinning solution (voltage 16 kV, syringe flow rate 0.8 mL / min, temperature 35° C., humidity 70%), taking it out after receiving it for 2 hours, and calcining it at 350° C. for 3 hours to obtain; The test showed that the porosity of the nanofiber membrane was 78% and the average fiber diameter was 215 nm.

[0032] Example 3 A hydrophobic perfluoro nanofiber membrane capable of catalytically degrading oily dyes is prepared by the following steps: S1, 9 kg of polyvinyl alcohol, 1.5 kg of modified carbon nanoparticles (prepared in Preparation Example 1), 1 kg of boric acid and 88.5 kg of perfluoropolymer dispersion (polytetrafluoroethylene dispersion, solid content 50%), stirred at 75 ° C for 2 h, defoamed in a vacuum oven, and obtained a spinning solution; S2, electrospinning the spinning solution (voltage 15 kV, syringe flow rate 1 mL / min, temperature 40° C., humidity 65%), taking it out after receiving it for 2 hours, and calcining it at 380° C. for 3 hours to obtain; The test showed that the porosity of the nanofiber membrane was 76% and the average fiber diameter was 218 nm.

[0033] Example 4 A hydrophobic perfluoro nanofiber membrane capable of catalytically degrading oily dyes is prepared by the following steps: S1, 15kg of polyvinyl alcohol, 2kg of modified carbon nanoparticles (prepared in Preparation Example 1), 1kg of boric acid and 83kg of perfluoropolymer dispersion (tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer dispersion, solid content 50%), stirred at 80°C for 2h, defoamed in a vacuum oven, and obtained a spinning solution; S2, electrospinning the spinning solution (voltage 18 kV, syringe flow rate 1 mL / min, temperature 35° C., humidity 70%), taking it out after receiving it for 2 hours, and calcining it at 370° C. for 5 hours to obtain; The test showed that the porosity of the nanofiber membrane was 75% and the average fiber diameter was 232 nm.

[0034] Example 5 A hydrophobic perfluoro nanofiber membrane capable of catalytically degrading oily dyes is prepared by the following steps: S1, 12kg of polyvinyl alcohol, 2kg of modified carbon nanoparticles (prepared in Preparation Example 1), 1kg of boric acid and 85kg of perfluoropolymer dispersion (tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer dispersion, solid content 60%), stirred at 80°C for 4h, defoamed in a vacuum oven, and obtained a spinning solution; S2, electrospinning the spinning solution (voltage 16 kV, syringe flow rate 0.9 mL / min, temperature 35° C., humidity 65%), taking it out after receiving it for 2 hours, and calcining it at 360° C. for 3 hours to obtain; The test showed that the porosity of the nanofiber membrane was 77% and the average fiber diameter was 235 nm.

[0035] Example 6 A hydrophobic perfluoro nanofiber membrane capable of catalytically degrading oily dyes is prepared by the following steps: S1, 12kg of polyvinyl alcohol, 1.5kg of modified carbon nanoparticles (prepared in Preparation Example 1), 0.8kg of boric acid and 85.7kg of perfluoropolymer dispersion (tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer dispersion, solid content 55%), stirred at 80°C for 2h, defoamed in a vacuum oven, and obtained a spinning solution; S2. The spinning solution is subjected to electrostatic spinning (voltage 12 kV, syringe flow rate 0.8 mL / min, temperature 40° C., humidity 65%), taken out after receiving for 2 hours, and calcined at 380° C. for 4 hours to obtain.

[0036] The test showed that the porosity of the nanofiber membrane was 76% and the average fiber diameter was 229 nm.

[0037] Comparative Example 1 A nanofiber membrane, which is different from Example 1 in that no modified carbon nanoparticles are added.

[0038] Comparative Example 2 A nanofiber membrane, which is different from Example 1 in that an equal amount of graphene (particle size 100 nm) is used instead of modified carbon nanoparticles.

[0039] Comparative Examples 3-4 A nanofiber membrane, which differs from Example 1 in that in step S1, the amounts of the components are different, as follows: Comparative Example 3: S1, 10 kg of polyvinyl alcohol, 0.5 kg of modified carbon nanoparticles (prepared by Preparation Example 1), 0.5 kg of boric acid and 89 kg of perfluoropolymer dispersion (polytetrafluoroethylene dispersion, solid content 40%), are stirred at 75°C for 2 h, and defoamed in a vacuum oven to obtain a spinning solution.

[0040] Comparative Example 4: S1. 10 kg of polyvinyl alcohol, 2.5 kg of modified carbon nanoparticles (prepared in Preparation Example 1), 0.5 kg of boric acid and 87 kg of perfluoropolymer dispersion (polytetrafluoroethylene dispersion, solid content 40%) were stirred at 75°C for 2 h, and defoamed in a vacuum oven to obtain a spinning solution.

[0041] Examples 7-11, Comparative Examples 5-6 A hydrophobic perfluoro nanofiber membrane capable of catalytically degrading oily dyes, which differs from Example 1 in that the usage of modified carbon nanoparticles is as shown in the table below, but the amount of modified carbon nanoparticles remains unchanged.

[0042] Table 1 Usage of modified carbon nanoparticles in Examples 7-11 and Comparative Examples 5-6 Example 7 8 9 10 11 Preparation example of modified carbon nanoparticles 2 3 4 5 6 Comparative Example 5 6 \ \ \ Comparative preparation example of modified carbon nanoparticles 1 2 \ \ \ Performance Testing The following performance tests were performed on the nanofiber membranes prepared in the examples and comparative examples, and the test results are recorded in Table 2.

[0043] Detection Methods 1. Water contact angle detection: At room temperature, 2 μL of water was dropped on the surface of the fiber membrane, and the water contact angle on the fiber membrane surface was recorded and measured using an optical contact angle meter (DSA100, Kruss). At least 5 positions of each fiber membrane were measured and the average value was taken as the water contact angle.

[0044] 2. Kerosene flux detection: The sample oil flux was tested by negative pressure filtration method: the fiber membrane was placed in the membrane pool fixture of the filtration bottle, 100 mL of kerosene was placed on the upper end, one end of the filtration bottle was connected to a vacuum pump, and after the vacuum pump was started (the pressure was adjusted to -0.05 MPa), the kerosene would pass through the membrane sample and be collected in the filtration bottle. The flux was calculated according to the following formula: Where J is the kerosene flux of the membrane sample (L·m -2 ·h -1 ), V is the volume of kerosene collected (L), A is the effective area of ​​the membrane pool (m 2 ), t is the operation time (h).

[0045] 3. Catalytic efficiency detection: The fiber membrane was placed in a 1 mg / L oily dye solution (Sudan III, the solvent was 50% ethanol aqueous solution), and the membrane sample was fully contacted with the dye in the solvent by magnetic stirring for 2 h. The absorbance of the photodegraded solution at 486 nm was then tested using a UV-visible spectrophotometer (TU-1810), and the catalytic efficiency was calculated using the following formula: Wherein, Ca is the absorbance of the original oily dye solution, Cb is the absorbance of the solution after the reaction, and E is the catalytic efficiency.

[0046] Table 2 Performance test results According to the data in Table 1, in Examples 1-6, the modified carbon nanoparticles prepared in Preparation Example 1 are used, so that the water contact angle of the prepared fiber membrane is large and the oil flux can reach up to 1433 L / m 2 ·h·bar, and the catalytic degradation rate of oily dyes is as high as 99.7%. However, in Comparative Example 1, no modified carbon nanoparticles are added, and in Comparative Example 2, unmodified carbon nanoparticles are used. The prepared fiber membranes have no catalytic degradation effect, and the oil flux is reduced. This shows that the modified carbon nanoparticles of the present application simultaneously improve the fiber membrane oil flux and catalytic degradation effect.

[0047] The difference between Comparative Examples 3-4 and Example 1 is that the amounts of the components of the spinning solution are different, and various properties are reduced.

[0048] The difference between Comparative Examples 5-6 and Example 1 is that copper nitrate is not added during the preparation of the modified carbon nanoparticles, or other nitrates are used instead of copper nitrate. The catalytic degradation effect of the prepared fiber membrane is significantly reduced to 20.1-32.2%, indicating that the catalytic degradation rate can only be improved by using copper nitrate / silver nitrate in the modified carbon particles.

[0049] The difference between Examples 7-11 and Example 1 is that the amounts of the components used in the preparation process of the modified carbon nanoparticles are different, and the fiber membranes within the range of Examples 7-11 also have higher oil flux and catalytic degradation rate.

[0050] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A hydrophobic perfluoro nanofiber membrane capable of catalytically degrading oily dyes, characterized in that: Obtained by electrospinning from spinning solution; The spinning solution is composed of the following components in weight percentage: Polyvinyl alcohol 9-15wt%; Modified carbon nanoparticles 1-2wt%; Boric acid 0.5-1wt%; Perfluoropolymer dispersion balance; The raw materials for preparing the modified carbon nanoparticles include carbon nanoparticles, cobalt nitrate hexahydrate, 2-methylimidazole, copper nitrate / silver nitrate and a solvent.

2. The hydrophobic perfluoro nanofiber membrane capable of catalytically degrading oily dyes according to claim 1, characterized in that: The preparation method of the modified carbon nanoparticles is: Cobalt nitrate hexahydrate and copper nitrate / silver nitrate are dispersed in a solvent to obtain a mixed solution A; carbon nanoparticles and 2-methylimidazole are dispersed in a solvent to obtain a mixed solution B; the mixed solution A and the mixed solution B are blended, reacted, centrifuged to remove the supernatant, washed, and dried to obtain the product.

3. The hydrophobic perfluoro nanofiber membrane capable of catalytically degrading oily dyes according to claim 2, characterized in that: In the mixed solution A, the concentration of cobalt nitrate hexahydrate is 8-20 mg / mL, and the concentration of copper nitrate / silver nitrate is 5-15 mg / mL.

4. The hydrophobic perfluoro nanofiber membrane capable of catalytically degrading oily dyes according to claim 2, characterized in that: In the mixed solution B, the concentration of carbon nanoparticles is 100-800 mg / mL, and the concentration of 2-methylimidazole is 50-70 mg / mL.

5. The hydrophobic perfluoro nanofiber membrane capable of catalytically degrading oily dyes according to claim 3, characterized in that: The carbon nanoparticles are one of nanographite powder, graphene, carbon nanotubes and fullerene.

6. The hydrophobic perfluoro nanofiber membrane capable of catalytically degrading oily dyes according to claim 1, characterized in that: The solvent consists of anhydrous methanol and anhydrous ethanol in a volume ratio of 7:

3.

7. The hydrophobic perfluoro nanofiber membrane capable of catalytically degrading oily dyes according to claim 1, characterized in that: The perfluoropolymer dispersion is one of a polytetrafluoroethylene dispersion and a tetrafluoroethylene-perfluoroalkoxy vinyl ether copolymer dispersion.

8. The hydrophobic perfluoro nanofiber membrane capable of catalytically degrading oily dyes according to claim 7, characterized in that: The solid content of the perfluoropolymer dispersion is 40%-60%.

9. A method for preparing a hydrophobic perfluoro nanofiber membrane capable of catalytically degrading oily dyes according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, blending polyvinyl alcohol, modified carbon nanoparticles, boric acid and perfluoropolymer dispersion, and defoaming to obtain a spinning solution; S2, electrospinning the spinning solution, and calcining at 350-380° C. for 3-5 h to obtain the product.

10. The method for preparing a hydrophobic perfluoro nanofiber membrane capable of catalytically degrading oily dyes according to claim 9, characterized in that: The specific parameters of the electrospinning are: voltage 12-18 kV, syringe flow rate 0.6-1.0 mL / min, temperature 35-40° C., and humidity 65-70%.